Measuring service performance for Urban Transformation Centre / Ummi Farhani Firdaus, Jasmine Ahmad, and Mahadir Ladisma @ Awis - Firdaus, Ummi Farhani; Ahmad, Jasmine; Ladisma @ Awis, Mahadir (Universiti Teknologi MARA, Shah Alam, 2017)
Service quality is much related to the customer satisfaction since it is one of the instruments to ensure the quality of the service that they provide to the customer is achieving the customer need. Enhancing service delivery to citizens at the centre had been identified in RMK 11 which is this plan are to within 2016-2020. This area is focused on supporting the government to transform the government service delivery become more effective and efficient in delivering the services to the public. Therefore, the government will put an effort in eliminating unnecessary bureaucratic process and ensure that the service that is being offered are more accessible and innovative. This is the reason why in Malaysia, the Urban Transformation Centre (UTC) had been introduced and becomes one of the service centers that provide integrated of services for the public or citizen. The purpose of this centre exist is to ensure that the public easy to access to the government service in one building without need to go to the other places and also to ensure that the public can receive the service during the weekend too. This paper aims to analyze service quality using SERVQUAL dimension and to suggest the specific items to measure service performance of UTC. All of the SERVQUAL dimensions which include of reliability, assurance, tangibility, empathy, and responsiveness had been explained in this paper which all of dimension is important to measure the customer satisfaction on UTC service performance.